2022
DOI: 10.1136/rmdopen-2022-002195
|View full text |Cite
|
Sign up to set email alerts
|

Sustained and improved guselkumab response in patients with active psoriatic arthritis regardless of baseline demographic and disease characteristics: pooled results through week 52 of two phase III, randomised, placebo-controlled studies

Abstract: ObjectivesTo evaluate the efficacy through 52 weeks of guselkumab, an interleukin 23-p19 subunit inhibitor, in subgroups of pooled psoriatic arthritis (PsA) patients from the DISCOVER-1 and DISCOVER-2 trials defined by baseline patient characteristics.MethodsAdults with active PsA despite standard therapies were enrolled in DISCOVER-1 (≥3 swollen and ≥3 tender joints, C reactive protein (CRP) level ≥0.3 mg/dL) and DISCOVER-2 (≥5 swollen and ≥5 tender joints, CRP ≥0.6 mg/dL, biological-naïve). Randomised patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 52 publications
3
11
0
Order By: Relevance
“…guselkumab, risankizumab) [ 49 52 ]. In clinical trials, however, this was not the case [ 53 , 54 ]. Considering these previously reported findings, along with the data presented here for TIL, a lower clinical response to all approved biological therapies is more likely in psoriasis patients with high BW, who may benefit from intensified dosing, which may be more difficult to accommodate with fixed-dose biological therapies.…”
Section: Discussionmentioning
confidence: 99%
“…guselkumab, risankizumab) [ 49 52 ]. In clinical trials, however, this was not the case [ 53 , 54 ]. Considering these previously reported findings, along with the data presented here for TIL, a lower clinical response to all approved biological therapies is more likely in psoriasis patients with high BW, who may benefit from intensified dosing, which may be more difficult to accommodate with fixed-dose biological therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Boehncke et al showed through the experimental results that people have poor memory in the spatial resolution learning task of the rotating platform and found that their LTP effect is poor [ 10 ]. At the same time, they found that even among the same group, there was a significant correlation between people's memory ability and their LTP response intensity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These results may not be generalisable to all patients with PsA; however, it should be noted that the treatment effect with guselkumab has been observed across subgroups from DISCOVER-1 and DISCOVER-2 defined by various baseline demographic and disease characteristics. 55 In addition, 2 years may be a relatively short follow-up time for observing radiographic progression in PsA. To that end, a phase 3b study (APEX; NCT04882098) is being conducted to further evaluate the effects of guselkumab on radiographic progression in at-risk biologic-naïve patients with PsA.…”
Section: Discussionmentioning
confidence: 99%
“…As noted, previous findings from DISCOVER-1 and DISCOVER-2 have demonstrated the efficacy of guselkumab in improving signs and symptoms across several PsA disease domains across diverse patient subgroups. 55 The patients with an elevated risk of future structural damage who were enrolled in DISCOVER-2 demonstrated low rates of radiographic progression through 2 years, with 85%–90% completing the study through week 100. Results of the current post hoc analyses from DISCOVER-2 indicate that achieving low levels of clinical disease activity, following 1 or 2 years of treatment with guselkumab, is associated with less radiographic progression over 2 years.…”
Section: Discussionmentioning
confidence: 99%